Endoscopic ultrasound-guided biliary drainage for malignant biliary obstruction after failed ERCP in low performance status patients. Issue 1 (January 2020) - Sassatelli, Romano; Cecinato, Paolo; Lupo, Marinella; Azzolini, Francesco; Decembrino, Francesco; Iori, Veronica; Sereni, Giuliana; Tioli, Cristiana; Cavina, Maurizio; Zecchini, Ramona; Parmeggiani, Francesca; Grillo, Simone; et al.
Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) with the placement of a biliary stent is the treatment of choice for palliation of malignant obstructive jaundice. In 5–10% of cases ERCP fails. In these cases an effective alternative is endoscopic ultrasonography-guided biliary drainage (EUS-BD). Aim: Evaluation of the principal clinical outcomes of direct transluminal EUS-BD. Patients and methods: This study is a retrospective analysis. All consecutive patients with malignant obstructive jaundice, in whom ERCP had failed, were enrolled. The primary outcome was the technical success of EUS-BD defined as the correct placement of the metal or plastic stent across the stomach or duodenum to the biliary tree. The most important secondary outcomes were early and late clinical success, both linked to the decrease of bilirubin haematic level. Results: Between January 2011 and November 2017 thirty-six patients were included. Technical success was obtained in 91.6%. A clinical success, early or late was obtained in 75.8%. The ECOG performance status of less than 3 was correlated with clinical success. Adverse events occurred in 30.3% of patients. Conclusions: EUS-BD is an effective and safe procedure.